Zooming Into Perspectives: High School Educators as They Adopt to In-person Education - Ramirez, Wealthia Hazel; De Leon, Meloddi Ciasih; Eligado, Sean Gabriel; Ganiban, Gabrielle Rose; Villa, Gianne Chelsea; Villarama, Joseph (Journal of Interdisciplinary Perspectives, 2024)
As there are few studies regarding teachers’ insights on online teaching, this study analyzed the adjustments of pandemic teachers shifting from online to in-person teaching methods to gain a deeper comprehension of the situations they experienced. This research conducted a descriptive qualitative case study following a researcher-designed, semi-structured interview with open and close-ended guide questions. Two participants were deduced to be the study participants, who were chosen through purposive sampling. Results revealed that the pandemic caused teachers’ depression and anxiety. Online learning has many drawbacks, as adopting online learning adds more pressure on struggling teachers to balance commitments. Their personal and professional lives collided, hindering their teachers’ effectiveness. Therefore, they learned to develop coping mechanisms to mitigate the stress. They also recognized the benefits of online learning and sought help to improve efficiency, as it helped them to see it from an alternate perspective. Despite the risks associated with COVID-19, they have shown resilience and dedication by positioning innovative teaching methods. As a preliminary exploration into the effects of the pandemic on the academic community, this study underscores continued research and support for educators and students. The commitment and passion demonstrated by these educators deserve recognition and celebration.